Development of an IoT Based Smart Door System with Access Control via WhatsApp - Adnan Buyung Nasution; Nugroho, Ahir Yugo; Gunawan, Heri; Sari, Ria Eka (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
Smart doors based on the Internet of Things (IoT) have become the focus of development in improving home security. This research aims to develop a smart door system that can be controlled via WhatsApp messages, exploiting the potential for collaboration between IoT and popular communication platforms. Development methods include hardware and software design, as well as secure integration of communication protocols. This system provides flexible and easy access control via the WhatsApp application, allowing homeowners to manage door access remotely. Experimental results show satisfactory performance in locking and opening the door, as well as responsiveness to commands via WhatsApp. This research details the development process, challenges faced, and potential implications in improving home security by utilizing IoT-based smart door technology.